PERAN TEKNOLOGI INFORMASI DALAM SUPERVISI PENDIDIKAN ANTARA EFISIENSI DAN HAMBATAN - Arif Wahyudi (JIP: Jurnal Ilmu Pendidikan, 2026)
This study aims to provide an in-depth analysis of the role of information technology in educational supervision, particularly in enhancing efficiency while identifying challenges that arise in the digital era, with a specific focus on vocational high schools. Using a qualitative research design with a case study approach, the research was conducted in several public vocational high schools in Banjarmasin, South Kalimantan. Data collection involved in-depth interviews with key stakeholders, direct observations of supervisory practices, and document analysis. The findings reveal that information technology significantly accelerates monitoring processes, strengthens accountability, and facilitates more effective communication between supervisors and teachers. However, several barriers were identified, including limited technological infrastructure, low levels of digital literacy among some educators, and resistance to changes in organizational work culture. The study concludes that information technology holds substantial potential to improve the quality of educational supervision. Nevertheless, its successful implementation depends on the readiness of human resources, consistent policy support, and the strengthening of digital capacity within schools. These results highlight the need for integrated strategies that combine technological innovation with professional development to ensure sustainable improvements in supervisory practices